KAJIAN DERET FIBONACCI DAN GOLDEN RATIO PADA LAGU BUNGAN SANDAT - YOGANGGA, GEDE AGUS HENDRA; IDA HARINI, LUH PUTU; NILA KENCANA, I PUTU EKA (E-Jurnal Matematika, 2012)
This study aims to analyze mathematically Bungan Sandat songs and arrange the elements in terms of the Fibonacci sequence and Golden Ratio. Then the ratio of the beauty of the song before and after arrangements were analyzed using the Wilcoxon test with 16 respondents from the student audience ISI Denpasar. Adjustment arrangements were made ??and given the title Bungan Sandat Fibo because it has proved to be a perfect Fibonacci sequence and Golden Ratio. Bungan Sandat Fibo song has the Fibonacci sequence contain up to 100% and the Golden Ratio is more perfect than the song before experienced arranger. In addition, based on the value of statistical tests, proven track Bungan Sandat Fibo more beautiful than Bungan Sandat song.
Keywords: Art; Fibonacci; Golden Ratio; Bungan Sandat Song